Zarządzanie zaufaniem w organizacjach zhierarchizowanych: Trust management in hierarchical organizations - Wyrębek, Henryk (Management and Administration Journal, 2021)
Trust plays an increasingly important role in the management of the organization. It is important for the quality of teamwork and leadership. The growing importance of confidence also stems from the fact that it is a way to mitigate risk and prevent uncertainty. These features make trust a particularly important value in the management of hierarchical organizations. To truly manage trust in an organization, you must understand the basics, in particular the process of its construction. This paper has a descriptive character and presents a source analysis. The paper presents: trust management concepts in organizations with hierarchical structures, principles of shaping trust in terms of utilitarianism, and the identification of factors affecting the trust management process.